Analisis Prosedur Pembuatan E-Invoice Angkutan Semen “Zak” pada PT Semen Indonesia Logistik - Syaharani, Tiara Putri; Vendy, Vicky (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This study aims to analyze the e-invoice creation procedure in the management of “zak” cement transportation at PT Semen Indonesia Logistik (SILOG), as part of the digital transformation in the billing system based on the urgency of the company's need for a more efficient and accurate billing system to reduce the risk of late payments and improve operational efficiency. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, direct observation, and documentation of four informants involved in the e-invoice creation process. The e-invoice creation procedure at SILOG involves the integration of the CSMS, FIOS, SAP, and PORTAL systems. The results of the study indicate that the implementation of e-invoices brings a number of advantages such as accelerating the billing process, time efficiency, reducing dependence on physical documents, and increasing data accuracy through a computerized system. However, this study also found significant technical constraints, especially in the accuracy of geofence data and unloading destinations that impact the validity of e-invoices. The FIOS system that is not yet optimal causes vehicle location data to sometimes not match the unloading point that should be. This constraint requires additional manual processes that can hinder the effectiveness of the system. Therefore, this study recommends improving the information system and technical training for users to reduce errors and increase the effectiveness of e-invoice use as a whole.